The Effectiveness of Using The Application of Pegadaian Digital Service to Easy Customer Transaction at Pegadaian Cirebon Branch - Sutarjo, Moh; Nurlia, Titim (Journal Socio Humanities Review, 2022)
The Pegadaian Digital Service application is a Pegadaian digital service in the form of a mobile-based application that can provide Pegadaian product services to make it easier for customers to make transactions anytime and anywhere. However, there are still many customers who carry out conventional transactions. This is the background for researchers to choose the title "Effectiveness of Using the Pawnshop Digital Service Application in Making Transactions Easier for Customers at Pawnshops Cirebon Branch." The purpose of this study is to determine the effectiveness of users transacting through the Pegadaian Digital Service application. This research uses descriptive qualitative method. The researcher used one key informant and four supporting informants. This study uses the theory of effectiveness measures by Campbell J.P. (1989:121) in Starawaji (2009) to be a guide in research. The results of the study can be concluded that judging from the success of the program, the success of the target, satisfaction with the program, the level of input and output, the achievement of overall goals is not optimal. And the data collection used by the researcher is a literature study and using field studies, namely observations and interviews.